ANALISIS PENGEMBANGAN PROFESIONALISME GURU PAUD BERDASARKAN PRESPEKTIF MAHASISW - Kamtini Kamtini; Anita Yus; Nasriah Nasriah; Salim Salim (JURNAL TEMATIK, 2020)
This study aims to create a picture of the professionalism of early childhood teachers based on the perspective of students of PGPAUD FIP Medan State University as seen from the students' perspectives on the indicators of PAUD teacher professionalism developed based on the results of research by Brock (2012). This type of research is descriptive quantitative. Data were collected using questionnaires and document analysis and analyzed using descriptive and qualitative analysis techniques. The results of the data analysis showed that the perspective of the PGPAUD FIP UNIMED students' perspective on the dimensions of PAUD teacher professionalism proposed by Brock was on average 94.57%. There are 3% indicators of the professional dimension of PAUD teachers proposed by Brock which are not approved by PGPAUD FIP UNIMED students and 2.5% do not make their choice. Further analysis results were discussed.